2017
DOI: 10.17957/ijab/15.0368
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bioethanol from Spoilage Date Fruits by New Osmotolerant Yeasts

Abstract: This research aimed at the production of bioethanol from a cheap and renewable resource (spoilage dates) by nonconventional yeasts to reduce total cost of the production. Chemical, physical or biological pretreatment of the spoilage date juice (SDJ) did not affect the availability of fermentable sugars significantly. The isolated osmotolerant yeast strains: Pichia kudriavzevii KKUY-0034, Hanseniaspora opuntiae KKUY-0152 and H. uvarum KKUY-0078, which were genetically identified based on sequences of D1/D2 doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The increase in the ethanol concentration in a 7-L fermenter could be related to various parameters that are affected by the scaling-up of a fermentation process such as the improved agitation and pH control. Indeed, in the 7-L-fermenter agitation was performed via mechanical stirring and not in a rotary shaker as in the flask experiments, resulting in more efficient mixing of the fermentation broth and consequently to better availability of the nutrients to the biocatalysts, leading thus to better productivities and yields [44]. Moreover, better mixing during the fermentation is reported to allow for more effective gas-liquid mass transfer [45] leading thus to better exchange of oxygen and fermentation gases [46] and also for more efficient heat transfer [47], which is expected to ensure optimal distribution of heat throughout the volume of the reactor.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the ethanol concentration in a 7-L fermenter could be related to various parameters that are affected by the scaling-up of a fermentation process such as the improved agitation and pH control. Indeed, in the 7-L-fermenter agitation was performed via mechanical stirring and not in a rotary shaker as in the flask experiments, resulting in more efficient mixing of the fermentation broth and consequently to better availability of the nutrients to the biocatalysts, leading thus to better productivities and yields [44]. Moreover, better mixing during the fermentation is reported to allow for more effective gas-liquid mass transfer [45] leading thus to better exchange of oxygen and fermentation gases [46] and also for more efficient heat transfer [47], which is expected to ensure optimal distribution of heat throughout the volume of the reactor.…”
Section: Discussionmentioning
confidence: 99%
“…Pratt-Marshall et al (2003) and Reddy and Reddy (2006) in separate studies showed that sugar concentrations increasing had a highly inhibiting effect on yeast growth and their capability to ethanol production [32,33]. This reduction is due to production of other compounds than ethanol and also rising of intracellular toxic ethanol concentration [34] which can stop the fermentation process and finally ethanol formation [35]. Several authors have used different Hanseniaspora strains in the fermentation processes.…”
Section: Discussionmentioning
confidence: 99%